Surface-induced spin state locking of the [Fe(H2B(pz)2)2(bipy)] spin crossover complex. (27th April 2016) - Beniwal, S; Zhang, X; Mu, S; Naim, A; Rosa, P; Chastanet, G; Létard, J-F; Liu, J; Sterbinsky, G E; Arena, D A; Dowben, P A; Enders, A
Abstract: Temperature- and coverage-dependent studies of the Au(1 1 1)-supported spin crossover Fe(II) complex (SCO) of the type [Fe(H2 B(pz)2 )2 (bipy)] with a suite of surface-sensitive spectroscopy and microscopy tools show that the substrate inhibits thermally induced transitions of the molecular spin state, so that both high-spin and low-spin states are preserved far beyond the spin transition temperature of free molecules. Scanning tunneling microscopy confirms that [Fe(H2 B(pz)2 )2 (bipy)] grows as ordered, molecular bilayer islands at sub-monolayer coverage and as disordered film at higher coverage. The temperature dependence of the electronic structure suggest that the SCO films exhibit a mixture of spin states at room temperature, but upon cooling below the spin crossover transition the film spin state is best described as a mix of high-spin and low-spin state molecules of a ratio that is constant. This locking of the spin state is most likely the result of a substrate-induced conformational change of the interfacial molecules, but it is estimated that also the intra-atomic electron–electron Coulomb correlation energy, or Hubbard correlation energy U, could be an additional contributing factor.